THE CONCEPT OF HOUSING WITH ARCHITECTURE BIOCLIMATIC APPROACH THAT CONSIDER HUMAN PERSPECTIVE TO OBTAIN A BETTER SETTLEMENT AND CONSERVATION ENERGY - Johanes Krisdianto; Ima Defiana; Irvansjah Irvansjah; Endy Yudho Prasetyo (Journal of Architecture&ENVIRONMENT, 2011)
Global warming is an issue that trend today. Awareness needed to perform its main energy efficiency is the energy cooling operations. Its because energy is related to the operational life of the thermal comfort of occupants to perform daily activities. This paper identifies residential design typology of house type 60 as a building envelope design and configuration space. The research determines the thermal performance and explore a simple house type 60 for its energy efficiency. In general, this paper aims to identify the typology of house type 60 that is associated with the operational cooling energy savings, as well as opportunities for what can be done to conserve energy by using architecture bioclimatic approach. The main benefits expected is to provide guidance on design concepts (via the model) based energy efficient cooling for modest residential type 60 in the humid tropics in order to conserve energy and create a healthy neighborhood. It need the dweller to adopt what they want to be in their own house. The fourth dimension in housing is a strenght that enable people to materialise their house to what they envisioned and using it to achieved what they intended to be.